Meticciamenti culturali e logiche di legittimazione istituzionale: il culto di Eufrosino in Chianti e i vescovi di Fiesole = Cultural Entanglements And Ecclesiastical Institution’s Legitimation: The Saint Euphrosino’s Cult Into The Chianti And The Bishops Of Fiesole - Gagliardi, Isabella (Hagiographica, 2023)
The veneration to Euphrosyne in the Fiesole episcopal territory is widely attested by 12th-century sources. Anyway the earliest hagiographic nucleus concerning him is found in the section of apostolic memoirs relating to the apostles Simon and Judas and attributed to Obadiah. That core was enriched by other tales such as the pilgrimage to Rome and then the arrival in Panzano, and this may have occurred in the Fiesole territory. Certainly the mention of Euphrosyne and his cult appears during the historical age when the Fiesole’s bishop needed to affirm the dignity of the bishopric and to reaffirm its special relations with Rome and the coeval process of Church Reform. The insistence on the apostolic origin and on the martyr matrix of the Fiesole church, in my opinion, should be read within these historical coordinates. So the process of promotion of the cult of Euphrosyne by the bishop of Fiesole, between the 11th and 12th centuries, happens when they need to defend the episcopate and the Fiesole territory from the aggressive maneuvers of Florence.